PERLINDUNGAN HUKUM TERHADAP PEKERJA ATAS HAK UPAH MINIMUM YANG BELUM SEPENUHNYA DIBAYAR (STUDI TERHADAP PUTUSAN NOMOR 58/K/PDT.SUS-PHI/2015) - Safira Khairani; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
Work and fair and proper remuniration are human rights of every person as stipulated on Article 28 D (2) The 1945 Constitution of The Republic Indonesia. Indonesia Law Number 13 Of 2003 regulates the rights and duties among entrepeneur and workers. Wage shall be received by worker/labourer as remuniration from entrepeneur. Labour Law provides the protection to wage as worker/labour’s right, stipulating that Government establishes a wage policy that protects the rights of worker/labourer such as Minimum Wage in order to fulfill every worker/labourer’s right to earn an income that meets livelihood that is decent for human. Labour Law also stipulates the wage will not be paid if worker/labourer do not perform work unless the worker/labourer has the will to do the job as promised but the entrepeneur does not employ them. The main issue in this research is the workers/labourers of PT. Srirejeki Perdana Steel claimed that they did not received full wage on November 2013 causing the amount of some of their wages lower than the amount of Minimum Wage set under valid statutory legislation. PT. Srirejeki Perdana Steel, postulated the reduction of the wage happened due to an illegal strike performed by the workers/labourers. The verdict on Industrial Relation Dispute Settlement of Bandung District Court and Indonesia Supreme Court did not grant the workers/labourers demand to get the fulfillment of their reducted wage. This research aims to acknowledge whether the protection towards workers/labors’s wage as verdicted by court followed the ruling as stipulated in Labourer Law.